The role of religiosity and self-efficacy towards a quarter-life crisis in Muslim college students - Hanifa Ihsani; Sabrina Etika Utami (INSPIRA: Indonesian Journal of Psychological Research, 2022)
Being a student is one of the phases of one’s development when entering the emerging adulthood phase. In the transition from adolescence to adulthood, people usually begin to experience problems in their lives. Those problems are generally related to the future. This study examines the role of religiosity and self-efficacy on a quarter-life crisis in Muslim college students. A total of 116 students from various universities in Padang participated in this study. Data were analyzed using multiple linear regression analysis. The results of this study indicate that the hypothesis is accepted. Religiosity and self-efficacy have a significant role in the quarter-life crisis. That means when religiosity and self-efficacy are high, the quarter-life crisis experienced by students decreases. This result has indicated by the calculated F value of 5.019 and a significance level of 0.008 (p<0.05). The contribution of religiosity and self-efficacy to the quarter-life crisis is 8.2%. This study also found that the partial contribution of religiosity did not have a significant role in the quarter-life crisis. On the other hand, the contribution of self-efficacy partially remains significant to the quarter-life crisis.